Time, space, and the authorisation of sex premises in London and Sydney. (February 2017) - Prior, Jason; Hubbard, Phil
While the regulation of commercial sex in the city has traditionally involved formal policing, recent shifts in many jurisdictions have seen sex premises of various kinds granted formal recognition via planning, licensing and environmental control. This means that 'sexual entertainment venues', 'brothels' and 'sex shops' are now not just labels applied to particular types of premises, but formal categories of legal land use. However, these categories are not clear-cut, and it is not simply the case that changes in the law instantiate a change whereby these premises are brought into being at a particular point in time. Countering the privileging of space over time that is apparent within much contemporary research on sex and the city, this paper foregrounds the varied temporalities in play here, and describes how the actions of those policy-makers, municipal bureaucrats and officers allow sex premises to variously 'fade in', accelerate, linger, or disappear as legal land uses within the city. We examine the implications of these different temporalities of the law by exploring how sex premises have been subject to regulation in London and Sydney, showing that the volatile, contradictory and fractured nature of legal space-making does not necessarily provide the certainty sought by the law but produces overlapping and contested understandings of what types of premises should be subject to regulation. More broadly the paper highlights how attention to the contingency and complexity of municipal law can help us better understand the ways that commercial sex is differently manifest in different cities.